Enhanced expression of endothelial nitric oxide synthase in the myocardium ameliorates the progression of left ventricular hypertrophy in L-arginine treated wistar-kyoto rats - Ahmad, A.; Sattar, M.A.; Rathore, H.A.; Abdulla, M.H.; Khan, S.A.; Abdullah, N.A.; Johns, E.J. (Polish Physiological Society, 2016)
The present study investigated the roleof endothelial nitric oxide synthase (eNOS) enzyme in the development of left ventricular hypertrophy (LVH) in Wistar-Kyoto rats. The effect of L-arginine administration on cardiac structure, arterial stiffness, renal and systemic hemodynamic parameters was studied and the change in expression of eNOS and cystathione g lyase (CSE) in the myocardium of LVH rats was evaluated. LVH was induced using isoprenaline (5 mg/kg, S.C.) and caffeine (62 mg/L in drinking water) for 14 days. Following to that, L-arginine (1.25g/L in drinking water) was given for 5 weeks as a donor of NO. eNOS and CSE gene expressions were down regulated in the LVH group by about 35% and 67% respectively when compared to control. However, in the LVH group treated with L-arginine there was up regulation of eNOS by almost 27% and down regulation in CSE by 24% when compared to control (all P < 0.05). Heart index and H2S plasma levels were reduced by almost 53% in the L-arginine treated LVH group compared to the control (all P < 0.05). Mean arterial pressure, heart rate and pulse wave velocity were reduced while renal blood perfusion increased in L-arginine treated LVH rats compared to their untreated counterparts (all P < 0.05). The enhanced expression of eNOS in L-arginine treated LVH rats resulted in the amelioration of oxidative and haemodynamic parameters suggesting that NO system is an important therapeutic target in cardiac and LV hypertrophies.